Effect of acute administration of nicotine and ethanol on tooth movement in rats - Cristiano Miranda de ARAUJO; Adriana Cristina ROCHA; Bianca Marques de Mattos de ARAUJO; Aline Cristina Batista Rodrigues JOHANN; Luiz Fernando PEREIRA; Orlando Motohiro TANAKA; Odilon GUARIZA FILHO; Elisa Souza CAMARGO (Sociedade Brasileira de Pesquisa Odontológica, 2018)
Abstract The aim of this study was to evaluate the effect of acute administration of nicotine and ethanol on tooth movement in rats. Two hundred rats were divided into eight groups: S: saline; N: nicotine; E: ethanol; NE: nicotine and ethanol; SM: saline with tooth movement; NM: nicotine with tooth movement; EM: ethanol with tooth movement; and NEM: nicotine and ethanol with tooth movement. All the solutions were applied for 32, 44, or 58 days, according to the subgroup. Orthodontic movement (25 cN) was initiated 30 days after solution administration in the groups with tooth movement. The rats were euthanized 2, 14, or 28 days after initiation of tooth movement. Tooth sections were stained using picrosirius and tartrate-resistant acid phosphatase (TRAP). The data were compared by ANOVA using Tukey's HSD and Games-Howell. On day 28 of tooth movement, the NEM group had a lower percentage of type I collagen compared to the SM group (p = 0.0448), and the S group had a higher number of osteoclasts/μm2 compared to the N group (p = 0.0405). Nicotine and ethanol did not affect the tooth movement rate, regardless of induction of orthodontic movement. Nicotine influenced the number of osteoclasts by decreasing their quantity when dental movement was not induced. When nicotine was associated with ethanol, it interfered in the maturation of collagen fibers during orthodontic movement.